The distribution of Baitul Mal aid fund for joint bussiness group program : is it effective? - Desi Tamida; Nanda, Nanda Safarida; Muhammad Dayyan (Prodi Manajemen Zakat dan Wakaf, Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Langsa, 2023)
Objective – This study aims to analyze the level of effectiveness, supporting and inhibiting factors as well as the impact of the distribution of aid funds by Baitul Mal to Joint Business Groups in Peureulak District, East Aceh. Method – This research collects primary data with interviewing the key informan from Baitul Mal East aceh and 5 beneficieries from each Joint Business Group Program (KUBE). Findings – The results of this study indicate that The level of effectiveness of the distribution of aid funds by East Aceh Baitul Mal to the Joint Business Group in Peureulak is considered to be still not optimal. This is assessed based on 4 main indicators, namely input, process, productivity, job satisfaction. Besides that, in its implementation, there are several supporting and inhibiting factors in efforts to distribute Joint Business Group (KUBE) assistance funds. The supporting factors include the availability of the latest information that is easily accessible to muzakki and mustahik, the presence of accompanying personnel and also the availability of a budget. Meanwhile, the inhibiting factors include inadequate facilities and infrastructure, still a lack of manpower, remote and difficult to reach locations and delays in sending files. Meanwhile, in terms of the impact of the distribution of aid funds, it is considered to be able to help increase the economic income of the poor, which at the same time helps the government in improving the country's economy. Limitation – The indicators used to measure the level of effectiveness are still too general. A more specific perspective is needed.Practical Implication – This researeh shows Through this research, it is hoped that it will be able to minimize the occurrence of misuse in the management of aid funds for Joint Business Groups. Thus it can optimize the achievement of goals, namely increasing the community's economy which will have an impact on increasing the standard of living and welfare of the Peureulak people.